(untitled) (Fiep Bulletin - online, 2014)
The study aims to present the contributions that ongoing formation relational feature to improve the pedagogical practice of physical education. The methodological approach favoured the qualitative approach. The journey undertaken in the investigation occurred along the lines of action research-engaged, which occurred in the course of training and teaching qualification: Weaving knowledge into motion for the teaching of physical education teachers for the Public Education Network of Fortaleza. Used as research instruments: questionnaires, interviews, texts and teachers’ transcripts of recordings of the course. To verify the changes, three aspects were considered for description of pedagogical practice: a) teaching methodology or the dynamics that teachers mobilize tract of the teaching-learning process, b) the teacher-student relation and c) privileged evaluation. It was possible to identify that the process of lifelong learning relational subsidized by ERP enhances the teaching qualification and contributes to significant changes in pedagogical practice of physical education.